2017
DOI: 10.3892/ol.2017.5617
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation and expression of Raf kinase inhibitory protein in esophageal squamous cell carcinoma

Abstract: Abstract. Raf kinase inhibitory protein (RKIP) regulates multiple cellular processes, and its downregulation is associated with distinct human cancers. In the present study, the status of RKIP promoter methylation, as well as its expression and clinical significance in esophageal squamous cell carcinoma (ESCC), were examined. The promoter methylation status in the 5'-CpG island of the RKIP gene and the expression level of the RKIP protein were examined using a modified methylation-specific polymerase chain rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
0
17
1
2
Order By: Relevance
“…Particularly, the absence of hypermethylation within the RKIP promoter is of therapeutic relevance, as this suggests that demethylating agents, including azacitidine and decitabine, do not display a promising therapeutic approach to restore RKIP expression. These data are in contrast to results from several solid tumors, where hypermethylation of RKIP has been demonstrated [68,69,70], and that show that the reasons for RKIP loss might be tissue-specific. To shed more light on the reasons for RKIP loss in AML, we screened for the deregulation of micro-RNAs (miRs).…”
Section: Rkip As a Therapeutic Target In Aml And Other Mnscontrasting
confidence: 99%
“…Particularly, the absence of hypermethylation within the RKIP promoter is of therapeutic relevance, as this suggests that demethylating agents, including azacitidine and decitabine, do not display a promising therapeutic approach to restore RKIP expression. These data are in contrast to results from several solid tumors, where hypermethylation of RKIP has been demonstrated [68,69,70], and that show that the reasons for RKIP loss might be tissue-specific. To shed more light on the reasons for RKIP loss in AML, we screened for the deregulation of micro-RNAs (miRs).…”
Section: Rkip As a Therapeutic Target In Aml And Other Mnscontrasting
confidence: 99%
“…RKIP loss also serves as a predictive marker for the progression and metastasis of liver [ 226 , 227 ], kidney [ 228 ], breast [ 229 ], ovarian [ 230 ], and colorectal cancers [ 231 ], as well as pancreatic ductal adenocarcinoma (PDAC) [ 232 ]. Combined with its promoter’s methylation, RKIP expression was further suggested as a biomarker of ESCC [ 233 ]. Phospho-RKIP was also reported as a predictive indicator of survival in lung cancer [ 234 ].…”
Section: Rkip As a Prognostic Indicator And A Therapeutic Targetmentioning
confidence: 99%
“…Promoter methylation: Promoter methylation is a well-characterized mechanism for epigenetic silencing by which gene transcription is halted through transcription factor inaccessibility, without any genetic alterations. Several studies of tumors, including gastric adenocarcinomas [ 18 , 19 ], esophageal squamous cell carcinomas [ 20 , 21 ], colorectal cancers [ 22 , 23 ], and breast cancers [ 24 ], reported that methylation status of the RKIP promoter determined by MSP (methylation specific PCR) strongly correlated with low RKIP expression levels in various advanced stages of the tumors. In gastric and esophageal cancers, carcinoma tissue showed significantly higher incidence rates of hypermethylated RKIP promoters than the adjacent normal mucosal tissue [ 19 , 21 ].…”
Section: Mechanisms Of Rkip Downregulation and Strategies For Recomentioning
confidence: 99%
“…In gastric and esophageal cancers, carcinoma tissue showed significantly higher incidence rates of hypermethylated RKIP promoters than the adjacent normal mucosal tissue [ 19 , 21 ]. In esophageal cancers, methylated promoter status also correlated with poorly differentiated tumors, as well as lymph node metastases [ 21 ]. In agreement with these findings, patients whose tumors had hypermethylated RKIP showed worse overall survival rates compared to unmethylated RKIP cases in gastric cancers [ 19 ], implicating RKIP as an independent prognostic marker for survival.…”
Section: Mechanisms Of Rkip Downregulation and Strategies For Recomentioning
confidence: 99%